Pengembangan Butir Soal Literasi Kimia pada Materi Sistem Koloid Kelas XI IPA SMA/MA - Wirna Eliza; Eka Yusmaita (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
This study aims to develop a chemical literacy instrument on colloidal system material that can be used to measure the literacy level of students. The research design on the development of this chemical literacy instrument uses the Model of Educational Reconstruction (MER). This research has several stages including content structure analysis (curriculum analysis, content analysis, context analysis, content validity by subject matter experts) and teaching and learning research (student interview investigation). The content validity test is carried out by five validators and the results will be analyzed by the Rasch model using the facet application. The results of this study indicate that the value of exact agreements is 88.9%, while the value of the expected agreements is 89.6% so it can be said that the results of the examiner's assessment are not much different from the expected results of the assessment